Corticosteroid-Sparing Effect of Chromoglycate Sodium and Nedocromil - A. F. Capristo; M. Miraglia del Giudice Jr; C. Alfaro; N. Maiello (Hindawi Limited, 1994)
The most appropiate management for bronchial asthma is the control of airway inflammation. Corticosteroids are the most effective anti-inflammatory drugs available, but they have a number of side effects; most of these are dose-dependent. In children, asthma control should be accomplished with low steroid doses possibly given by inhalation. In a double-bind placebo-controlled crossover study a group of children with mild to moderate asthma received NED 16 mg/day or BDP 400 μg/day. Values for FEV1, PEF, symptoms use ofbronchodilators overlapped, whereas bronchial hyper-responsiveness assessed by histamine bronchoprovocation challenge was better with BDP than NED. In another case, one boy with high bronchial hyper-reactivity assessed by provocation test with hypertonic solution, experienced a significant improvement only after 2 weeks of therapy with Deflazacort (2 mg/Kg/day) followed by 4 months on combined treatment with NED (16 mg/day) and BDP (300 μ/day). Authors conclude that NED could have a steroidsparing effect over long-term use.